Satisfaction and continuation intention in music streaming services: investigating key factors for user retention - Li, Qianwen; Liu, Yapu; Chen, Chen (Frontiers in Psychology, 2025)
BackgroundThe business landscape for music streaming services has shifted significantly over the past decade. Retaining music streaming users is critical for service providers' sustainability.MethodsThis study utilized an electronic questionnaire to survey 895 music streaming users. Structural equation modeling was conducted using Smart-PLS software to investigate the factors influencing service satisfaction and continuation intention among music streaming users. This study is grounded in the Expectation Confirmation Model and builds upon the theoretical foundation of the Information System Success Model as well as prior research. To enhance the analytical framework, four key variables have been incorporated: information quality, system quality, service quality, and perceived fair pricing. This extension aims to provide a more comprehensive understanding of the factors influencing user satisfaction and continuation intention, thereby offering a systematic theoretical framework for examining user behavior within the context of music streaming services.ResultsThe study showed that service satisfaction plays a central role in driving continuation intention, emphasizing its importance for user retention. Perceived usefulness was found to significantly impact service satisfaction, which in turn influenced users' intention to continue using the service. Expectation confirmation was a key determinant of service satisfaction, but it did not directly affect perceived usefulness, suggesting that user expectations in the context of music streaming services are more influenced by content availability and user experience than by platform functionality. Additionally, perceived fair pricing, information quality, and system quality all contributed to higher levels of service satisfaction and perceived usefulness, reinforcing their critical role in enhancing user engagement and retention in a competitive market.ConclusionThis study can provide guidance for music streaming service providers to improve user retention and payment rates.